Study on Quality of Some Types of Fabrics from Men’shirts Produced and Sold in the Vietnam - Vu, Thi Hong Khanh; Tran, Thi Hong Minh (Old Journal, 2018)
This paper presents the result of study on quality of three fabrics used to make men’shirts for the Vietnamese market. These three fabrics are made from three types of men’s shirts sold in the May 10 chain. These three types of men’s shirts are manufactured by Garment 10 Coporation, they represent three major product lines of men’shirt in the Vietnamese market: hight class, middle class and popular class. The quality of of these 3 fabrics has been evaluated and compared by differetial method and by method using the total quality index. The quality criterie list of the men’s shirt fabric and important coefficient of each criteria are determined by the expert method. The study results show that the fabric of hight class men’s shirt has the best quality in comparison with other two.